Psychological Stress Up-Regulates CD147 Expression Through Beta-Arrestin1/ERK to Promote Proliferation and Invasiveness of Glioma Cells - Wang, Ping; Wang, Zhenming; Yan, Yizhi; Xiao, Lin; Tian, Wenxiu; Qu, Meihua; Meng, Aixia; Sun, Fengxiang; Li, Guizhi; Dong, Junhong (Frontiers in Oncology, 2020)
Psychological stress is closely related to the occurrence and prognosis of various malignant tumours, but the underlying mechanisms are not well studied. CD147 has been reported to be expressed in glioma and other malignant tumours. CD147 not only participates in lactic acid transport, but it also plays an important role in the invasion and metastasis of malignant tumour cells by stimulating the production of numerous matrix metalloproteinases (MMPs) and vascular endothelial growth factor by fibroblasts. Here, we found that silencing CD147 in chronically stressed nude mice not only inhibited the proliferation of xenografts but also decreased matrix metalloproteinase-2 expression and lactic acid content in tumour tissues. Furthermore, norepinephrine (NE) was significantly increased in the serum of nude mice in our glioma stress model. To determine the underlying cellular mechanism, we added exogenous NE into glioma LN229 cells to simulate the stress environment in vitro, The invasiveness of the glioma cells was subsequently examined using a Matrigel invasion assay. We demonstrated that knockdown of CD147 inhibited glioma invasiveness and metastasis with norepinephrine stimulation. Luciferase reporter gene experiments further demonstrated that the expression of CD147 is up-regulated primarily by norepinephrine via the β-Adrenalin receptor (βAR)-β-arrestin1-ERK1/2-Sp1 pathway. High expression of CD147 promoted the secretion of MMP-2 and the increment of lactic acid, which accelerated the augmented invasion and metastasis of glioma induced by psychological stress. Taken together, these results suggest that psychological stress promotes glioma proliferation and invasiveness by up-regulating CD147 expression. Thus, CD147 might be a potential target site in the treatment of glioma progression induced by chronic psychological stress.